GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 1266 species occurrences available in GBIF matching the query: TaxonKey: Parmelina quercina (Willd.) Hale HasCoordinate: TRUE HasGeospatialIssue: FALSE. The dataset includes 1266 records from 36 constituent datasets: 23 records from BLS Rare and Threatened Lichen Records: Wales. 1 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 50 records from Colección de líquenes del Herbario "Jaime Andrés Rodríguez". LEB-Lichen. 2 records from BLS Lichen Database: English churchyards. 18 records from Australia's Virtual Herbarium. 1 records from iNaturalist Research-grade Observations. 5 records from Institut Botanic de Barcelona (IBB-CSIC-ICUB), BC-Lichen. 2 records from INPN - Données flore des CBN agrégées par la FCBN. 2 records from Lichen herbarium, Oslo (O). 1 records from IBF Monitoring of Lichens. 10 records from Natural History Museum (London) Collection Specimens. 29 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 52 records from Herbarium Senckenbergianum (FR) - Fungi. 6 records from Canadian Museum of Nature Herbarium. 27 records from Real Jardin Botanico, Madrid: MA-Lichen. 22 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 2 records from Michigan State University Herbarium Lichens. 90 records from Arizona State University Lichen Collection. 34 records from Lichen Herbarium Berlin. 62 records from Biologiezentrum Linz. 120 records from LiquenCAT: Banco de datos de los líquenes de Cataluña. 14 records from Epiphytic Lichens of G. Lettau at the Botanical Museum Berlin-Dahlem. 5 records from Countryside Council for Wales - Lichens of Conservation Concern - Site Data, Wales. 61 records from Universitat de València, Colecciones de Criptógamas: VAL_Lich. 12 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 1 records from Natural History Museum, University of Tartu. 2 records from Herbarium of Umeå University (UME). 167 records from BLS Lichen Database: England. 2 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 149 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 87 records from BLS Mapping Scheme dataset, 1750-2009. 25 records from BLS Lichen Database: Wales. 35 records from Lund Botanical Museum (LD). 143 records from BLS Rare and Threatened Lichen Records: England. 3 records from Geneva Herbarium – General Collection (G). 1 records from Lichen herbarium, UiB. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences